2019
DOI: 10.1016/j.jjcc.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Serum malondialdehyde-modified low-density lipoprotein levels on admission predict prognosis in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Accumulating evidence has shown that oxidized low-density lipoprotein (LDL) is a useful marker for cardiovascular disease. Oxidized LDL contributes to atherogenesis in a wide range of stages, such as impairing vascular endothelial cells, promoting expression of adhesion factors of vascular endothelial cells, and facilitating monocyte migration and accumulation of lipids under the vascular endothelium by being captured by macrophages [1]. Previous studies have shown that oxidized LDL levels are elevated in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Malondialdehyde-modified low-density lipoprotein (MDA-LDL) is similar to ox-LDL and represents one of the major products of lipid peroxidation [ 43 ]. Research conducted by Amioka and colleagues (2019) revealed the association of high MDA-LDL levels with AMI compared to those with unstable angina.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Malondialdehyde-modified low-density lipoprotein (MDA-LDL) is similar to ox-LDL and represents one of the major products of lipid peroxidation [ 43 ]. Research conducted by Amioka and colleagues (2019) revealed the association of high MDA-LDL levels with AMI compared to those with unstable angina.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Acute myocardial infarction inevitably causes ischemic–anoxic myocardial injury, which induces intensive ROS production [ 55 ]. Since MDA levels correlate with AMI severity, this indicator has been used as a determinant of severe coronary diseases [ 56 ]. Moreover, it was also shown that lipid peroxidation levels measured in patients’ plasma positively correlated with the severity of dilated cardiomyopathy symptoms [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher MDA levels are related to ischemic damage or unstable plaque in ACS patients [27] . Moreover, MDA levels were correlated with the AMI rate, and MDA levels have been used as a determinant for severe coronary diseases [28] . Nand et al reported that MDA levels in an AMI group increased three-fold compared to those of healthy individuals [8] .…”
Section: Discussionmentioning
confidence: 99%